Using parallel computing technologies in graphics processors for stream cipher generators - Полуяненко, Н.А.; Потий, А.В. (Radiotekhnika, 2017)
The possibility of transferring a part of the computational process from the central processing unit to the graphics processing unit with help of software platform, using of technology in organization of concurrent computing with GPU NVIDIA CUDA is considered. Comparison of performance of the nonlinear feedback shift registers generation on CPU and GPU is carried out.